Intra-abdominal desmoplastic small round cell tumour - Ansari, NP; Mamun, MA; Islam, MS; Begum, A (Community Based Medical Journal, 2013)
Intra-abdominal desmoplastic small round cell tumour (DSRCT) is a rare and highly aggressive malignant neoplasm with a strong predilection in young male adults. and frequently presents as a large abdominal mass .Here, we present a case of DSRCT in a 40 years male with mild ascitis. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16704 Community Based Medical Journal 2013 July: Vol.02 No 02: 75-77